2020
DOI: 10.1039/d0py00939c
|View full text |Cite
|
Sign up to set email alerts
|

Recent development in halogen-bonding-catalyzed living radical polymerization

Abstract: The development and applications of an organocatalyzed living radical polymerization via halogen-bonding catalysis, i.e., reversible complexation mediated polymerization (RCMP), are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 138 publications
(176 reference statements)
0
53
0
Order By: Relevance
“…The preparation of polymers with precise structure by photosynthesis is ubiquitous in nature. [ 1,2 ] Photo‐controlled reversible‐deactivation radical polymerization (RDRP) techniques, represented by atom transfer radical polymerization (ATRP), [ 3–6 ] reversible addition‐fragmentation chain‐transfer (RAFT) polymerization, [ 7–9 ] nitroxide‐mediated polymerization, [ 10 ] and reversible complexation‐mediated radical polymerization, [ 11–15 ] have made great advancement for the construction of various functional polymers with pre‐designable molecular weight and narrow molecular weight distribution. [ 16,17 ] Due to the mild polymerization condition, low side reaction and spatiotemporal control of photo‐controlled RDRP techniques, [ 18,19 ] various polymerization strategies have been developed including oxygen‐tolerance radical polymerization or using oxygen as co‐catalysts, [ 20–23 ] metal‐free radical polymerization under visible light even near‐infrared lights, [ 24–27 ] and photo/electro mediated sequential polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of polymers with precise structure by photosynthesis is ubiquitous in nature. [ 1,2 ] Photo‐controlled reversible‐deactivation radical polymerization (RDRP) techniques, represented by atom transfer radical polymerization (ATRP), [ 3–6 ] reversible addition‐fragmentation chain‐transfer (RAFT) polymerization, [ 7–9 ] nitroxide‐mediated polymerization, [ 10 ] and reversible complexation‐mediated radical polymerization, [ 11–15 ] have made great advancement for the construction of various functional polymers with pre‐designable molecular weight and narrow molecular weight distribution. [ 16,17 ] Due to the mild polymerization condition, low side reaction and spatiotemporal control of photo‐controlled RDRP techniques, [ 18,19 ] various polymerization strategies have been developed including oxygen‐tolerance radical polymerization or using oxygen as co‐catalysts, [ 20–23 ] metal‐free radical polymerization under visible light even near‐infrared lights, [ 24–27 ] and photo/electro mediated sequential polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by research from Fu, 205 Goto, 191,206 Zhu 207 and Matyjaszewski's 208 on iodine‐mediated photoATRP, Lei and coworkers developed an innovative approach that took advantage of organocatalysts and sodium iodide (NaI) under white LED irradiation to catalyze ROP and iodine‐mediated photoATRP, respectively 44 . Simultaneously, it was demonstrated that 1,1,3,3‐tetramethylguanidine (TMG) organocatalysts combined with NaI could facilitate ROP of cyclic ester monomers like the LLA and photoATRP initiated from difunctional initiators such as 2‐hydroxyethyl‐2‐bromo‐2‐phenylacetate (Br‐Ph‐OH; Figure 21).…”
Section: Polymerization Methodologies Mediated Using Orthogonal External Stimulimentioning
confidence: 99%
“…The polymerization is initiated by halide abstraction using a XB donor (Scheme 10). Interestingly, while iodine(I) based XB donors have also been used in such a reaction a few years ago [96–98] diaryliodonium salts actually have a long history as photoacids of polymerization [99] . The use of the latter as Lewis acid in such a transformation was however never explored.…”
Section: Applications In Organocatalysismentioning
confidence: 99%